2021
DOI: 10.21203/rs.3.rs-303940/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Community Characteristics of Sympatric Freshwater Turtles From Savannah Waterbodies in Ghana

Abstract: Despite increasing pressures on freshwater resources worldwide, and the threatened status of most freshwater turtles, there is still limited knowledge of habitat use and niche partitioning in Afrotropical freshwater turtle communities. In this study, we describe habitat associations, community diversity, and temporal patterns of occurrence of freshwater turtle species in the Dahomey Gap ecoregion of Ghana (West Africa). We gathered data from 13 sites in central Ghana and along the Sene Arm of Lake Volta in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…Also recent studies from Ghana and Benin revealed a number of species (in Ghana 3 for shrews and 12 for rodents; in Benin 2 for shews and 10 for rodents) that is consistent with our analyses (Nicolas et al 2020;Decher et al 2021), and the same is true for rodent communities in Malawi (9 sympatric species; Happold and Happold 1991). Interestingly, a relatively stable number of sympatric species per site was also seen in turtles from West African savannahs (Gbewaa et al 2021), thus suggesting that the ecological conditions of the various West African savannah sites are functionally similar and support a inter-site similar number of sympatric species although not necessarily the same taxa.…”
Section: Conflict Of Interestsupporting
confidence: 91%
“…Also recent studies from Ghana and Benin revealed a number of species (in Ghana 3 for shrews and 12 for rodents; in Benin 2 for shews and 10 for rodents) that is consistent with our analyses (Nicolas et al 2020;Decher et al 2021), and the same is true for rodent communities in Malawi (9 sympatric species; Happold and Happold 1991). Interestingly, a relatively stable number of sympatric species per site was also seen in turtles from West African savannahs (Gbewaa et al 2021), thus suggesting that the ecological conditions of the various West African savannah sites are functionally similar and support a inter-site similar number of sympatric species although not necessarily the same taxa.…”
Section: Conflict Of Interestsupporting
confidence: 91%